A Rare Case of Abdominally Placed, Non-communicating Tubal Pregnancy with Unicornuate Uterus - Çepni, İsmail; Özçivit, İpek Betül; Biçer, Elifnur; Yıldırım, Mehmet; Doğancı, Özge Irmak; Madazlı, Rıza; İlvan, Şennur (Cerrahpaşa Medical Journal, 2022)
This case report aims to present a very rare case of abdominal pregnancy localized in the non-communicating fallopian tube in a patient with a unicornuate uterus. A 32-year-old patient presented with abdominal pain and high beta-human chorionic gonadotrophin levels and was suspected of ectopic pregnancy. Diagnostic laparoscopy revealed unicornuate uterus with a normal fallopian tube and ovary on the left side. On the contralateral side, right ovary and fallopian tube were explored adherent to the abdominal wall as well as the tubal ectopic focus in the non-communicating fallopian tube. Then, salpingectomy was performed. The female reproductive system was formed by the migration and fusion of bilateral Müllerian ducts. Due to the incomplete transabdominal descent of the ovary, the ipsilateral Müllerian duct could not complete its caudomedial development and failed to fuse and form the uterovaginal primordium in this patient, resulting in a unicornuate uterus and an abdominal ovary and fallopian tube. Interestingly, ectopic pregnancy occurred in the abdominally placed non-communicating fallopian tube in this case. To our knowledge, this is the first case to report an ectopic pregnancy that occurred in an abdominally placed non-communicating fallopian tube in a patient with unicornuate uterus. Ectopic pregnancy is an important complication of Mullerian duct anomalies and should be diagnosed and treated early by laparoscopy. Cite this article as: Çepni I, Özçivit İB, Biçer E, et al. A rare case of abdominally placed, non-communicating tubal pregnancy with unicornuate uterus. Cerrahpaşa Med J. 2022;46(2):168-171.